Selection of suitable stain in Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) for the control of biological management of Chrysodeixis includens (Lepidoptera: Noctuidae) - da Silva Ponce, Franciely; de Oliveira, Moisés Daniel; De Carvalho, Vanessa Rafaela; de Lima Toledo, Claudia Aparecida; Seabra Júnior, Santino; de Oliveira, Regiane Cristina (Journal of Asia-Pacific entomology, 2025)
[Display omitted] •“FT” presented more as the longevity and number of T. pretiosum adults per parasitized egg.•Flight- and walk-defective individuals were more prevalent in “SB I and II”.•The combination of Cardinium, Spiroplasma, and Serratia endosymbionts may have favored a higher percentage of females and longevity. Selection of suitable Trichogramma strain is critical in biological control programs against pests. Thus, the objective was to select the most suitable strains based on the biological and molecular analyses of five populations of T. pretiosum to develop the program of biological control of C. includens in brassica cultivation. A randomized complete block design was used, with five strains (FT, VI, VII, SBI and SBII) and 20 replicates. Endosymbionts present in the strains were identified by polymerase chain reaction. “FT” showed better longevity, a higher number of adults per egg, and a higher sex ratio compared to the other strains. It was the most indicated for the biological control of C. includens in brassicas despite failing to obtain the highest egg parasitism. Cluster analysis showed that the “FT” strain met a majority of the requirements for managing C. includens and flying pests. Among the evaluated endosymbionts, Cardinium, Carsonella, Spiroplasm, and Serratia were observed in three of the five evaluated strains, and a combination of Cardinium, Spiroplasma, and Serratia may be involved in the parasitism of the “FT” strain.